Practical Text Analytics Maximizing the Value of Text Data - Anandarajan, Murugan; Hill, Chelsey; Nolan, Thomas (Advances in Analytics and Data Science, 2019)
XXVIII, 285 p. 265 illus., 157 illus. in color.